2011
DOI: 10.1108/02640471111177080
|View full text |Cite
|
Sign up to set email alerts
|

An investigation and analysis of the application of Web 2.0 in Chinese university libraries

Abstract: PurposeThis paper aims to provide an overall picture of the application of Web 2.0 technologies in Chinese university libraries. The focus of the research is what types of Web 2.0 technologies were applied in such libraries as well as their function and user interface.Design/methodology/approachThe top 30 Chinese university libraries were selected to investigate the application of Web 2.0 technologies. Content analysis was used in terms of quantitative approach. Data were collected by accessing these 30 univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 9 publications
(7 reference statements)
1
15
0
Order By: Relevance
“…Today, the use of social media in libraries is widespread (Jahan & Ahmed, 2012;Kim & Abbas, 2010;Linh, 2008;Si, Shi, & Chen, 2011). Studies demonstrate that some university library digital resources and services are fully utilized and developed through social media tools (Harinarayana & Raju, 2010;Liu, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Today, the use of social media in libraries is widespread (Jahan & Ahmed, 2012;Kim & Abbas, 2010;Linh, 2008;Si, Shi, & Chen, 2011). Studies demonstrate that some university library digital resources and services are fully utilized and developed through social media tools (Harinarayana & Raju, 2010;Liu, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social networking sites, Blogs, microblogs, RSS, instant messaging, mashups, podcasts, and vodcasts were widely used. Si, Shi and Chen 25 showed that majority of the Chinese university libraries used one or more web 2.0 tools in their websites. Boateng and Liu 26 revealed that all the 100 top US academic libraries had links to Facebook and Twitter in their websites.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Google Apps were mainly used for archiving information whereas YouTube was singled out as used for entertainment. Olasina (2011) notes that social media tools such as YouTube are powerful tools for leisure and, similarly, Si, Shi and Chen (2011) comment that tools such as wikis and RSS feeds are mostly used for searching for information and following current events respectively. Trubitt and Overholtzer (2009: 91) state that librarians have incorporated these applications into their daily routines, using "Facebook, Twitter, LinkedIn, online gaming environments, and other tools to build and maintain complex webs of professional and personal relationships".…”
Section: Personal Uses Of Social Media By Librariansmentioning
confidence: 99%